Church and culture? : exploring the reception of women’s ministries in the Reformed Church in Zambia in view of 1 Corinthians 14:26-40 - Phiri, Jackson (Stellenbosch : Stellenbosch University, 2017)
Thesis (PhD)--Stellenbosch University, 2017.